2018
DOI: 10.1039/c8ra06025h
|View full text |Cite
|
Sign up to set email alerts
|

Schwertmannite: occurrence, properties, synthesis and application in environmental remediation

Abstract: Schwertmannite is a typical iron-derived mineral, which was originally discovered in acid mine drainings and subsequently synthesized in the laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 100 publications
1
20
0
Order By: Relevance
“…43 The presence of schwertmannite may also be caused by the ammonia leaching out of the catalyst 30 into the impregnating solution leading to the iron(III) sulphate precipitating into schwertmannite. 42 In regards to the removal of iron from Fe-T2 with EDTA in Section 3.3, as schwertmannite is more soluble compared to goethite due to its poor crystallinity, it is more likely to be dissolved by EDTA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 The presence of schwertmannite may also be caused by the ammonia leaching out of the catalyst 30 into the impregnating solution leading to the iron(III) sulphate precipitating into schwertmannite. 42 In regards to the removal of iron from Fe-T2 with EDTA in Section 3.3, as schwertmannite is more soluble compared to goethite due to its poor crystallinity, it is more likely to be dissolved by EDTA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…for Res-(Fe-T2). 42 Other than schwertmannite, there is a major presence of goethite. The presence of the SO 4 2À peak in the spectra is due to the residual Fe 2 (SO 4 ) 3 and Na 2 SO 4 from impregnation from which some schwertmannite has been produced.…”
Section: àmentioning
confidence: 99%
“…EDS data for the final schwertmannites are exhibited in Table 1 (SO 4 ) x , 1 x 1.86) with a Fe/S mole ratio ranging in 4.3-8.0. [1][2][3][4] Also, EDS data showed that within a shorter cellular cultivation period of 36 h, the absence of Cl À was examined in all schwertmannite products.…”
Section: Morphological Evolution Of Schwertmannitesmentioning
confidence: 99%
“…[1][2][3] The key issues for schwertmannites, such as synthetic strategies, structure-property relationships, potential environmental applications, and related mechanisms, have been recently overviewed. 4 It has been accepted that schwertmannites are effective scavengers [5][6][7][8] and environmentally potential adsorbent materials of metals/ metalloids, [9][10][11][12][13] rare earth elements, 14 and fluoride. 15 However, schwertmannites as an unstable phase will progressively transform into other stable iron mineral phases of jarosite and goethite, releasing an appreciable amount of acidities and bound trace metals, due to variation of pH and acid concentration, 2,3 and the presence of aqueous Fe(II) and dissolved organic matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation